2017
DOI: 10.1016/j.smallrumres.2016.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genetic diversity and structure of major sheep breeds from Pakistan

Abstract: The present study aimed at the genetic characterization of major economically important sheep (Ovis aries) breeds from Pakistan. A total of 155 sheep from five breeds, Balkhi (PBS), Kaghani (PKS), Damani (PDS), Salt Range (PSS) and Thalli (PTS) were analyzed for measures of genetic variability, differentiation and population structure. All the five breeds exhibited moderate to high levels of genetic diversity, with an average observed heterozygosity of 0.631 ± 0.043. The mean estimates of measures of genetic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
1
0
3
Order By: Relevance
“…Estimates were also comparable with that of the Kajali sheep, that belong to the NWASA region 21 and four sheep populations of the SP region; Madras Red, Mecheri, and Pattanam 27 and Tiruchi Black 28 . The genetic variability observed in this study was higher than those reported in Jordan sheep 29 , and sheep breeds of the neighboring country, Pakistan 30 . However, it was comparable to the values reported across the world, for sheep 31,32 .…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Estimates were also comparable with that of the Kajali sheep, that belong to the NWASA region 21 and four sheep populations of the SP region; Madras Red, Mecheri, and Pattanam 27 and Tiruchi Black 28 . The genetic variability observed in this study was higher than those reported in Jordan sheep 29 , and sheep breeds of the neighboring country, Pakistan 30 . However, it was comparable to the values reported across the world, for sheep 31,32 .…”
Section: Discussioncontrasting
confidence: 83%
“…F ST values of the examined Indian sheep breeds were comparable to those reported for Baltic, Chiapas, and Akkarman sheep 33 . However, it was much higher than the F ST values reported for several others like Spanish, European, Middle Eastern, Colombian, Pakistani, and Romanian sheep breeds 30,32,37 . Much lower differentiation (5.6-5.9%) has been reported in Indian sheep breeds of SP region 15,27 .…”
Section: Discussioncontrasting
confidence: 61%
“…Mean number of alleles per breed was similar to the study of Tolone et al (2012), who analysed Comisana, Pinzirita, Sarda and Valle del Belice Sicilian breeds and reported values from 5.66 to 9.44. Mean number of alleles per locus across analysed breeds was also in agreement with the study of Naqvi et al (2017) in Pakistan breeds (5.73 to 7.62), Othman et al (2016) in local Egyptian breeds (5.82 to 8.18) and Loukovitis et al (2016) in 13 local Greek breeds (4.59 to 7.34).…”
Section: Resultssupporting
confidence: 87%
“…In the present study, the calculated MNa values belonging to Algerian sheep populations studied were found to be higher than the values stated in some studies on domestic and foreign breeds (Gaouar et al, 2016b;Loukovitis et al, 2016;Naqvi et al, 2017) but MNa values observed in Turkish sheep breeds were lower than those of native sheep breeds raised in Tunisia (Sassi-Zaidy et al, 2016). This is thought to be due to the difference in the number of microsatellites and sampling methodology used in this study.…”
Section: Discussioncontrasting
confidence: 85%